Clinical approach to renal diseases in diabetes - Dhinakaran T (New Delhi Jaypee Brothers Medical Publishers, 2015)
Clinical Approach to Renal Diseases in Diabetes highlights the development of diabetes mellitus, renal involvement and other comorbid conditions along with the latest therapeutic regimens. Covers all aspects of renal involvement in diabetes, providing a useful resource to general practitioners, urologists, nephrologists and diabetologists.
Keywords: Diabetes Complications -- Diabetic neuropathies -- Kidneys Diseases